3D printed MOF-based mixed matrix thin-film composite membranes. Issue 41 (26th July 2021) - Elsaidi, Sameh K.; Ostwal, Mayur; Zhu, Lingxiang; Sekizkardes, Ali; Mohamed, Mona H.; Gipple, Michael; McCutcheon, Jeffrey R.; Hopkinson, David
Abstract : An electrospray 3D printing approach for fabricating thin-film composite mixed-matrix membranes (TFC MMM) with a thickness of 2–3 μm. Abstract : MOF-based mixed-matrix membranes (MMMs) have attracted considerable attention due to their tremendous separation performance and facile processability. In large-scale applications such as CO2 separation from flue gas, it is necessary to have high gas permeance, which can be achieved using thin membranes. However, there are only a handful of MOF MMMs that are fabricated in the form of thin-film composite (TFC) membranes. We propose herein the fabrication of robust thin-film composite mixed-matrix membranes (TFC MMMs) using a three dimensional (3D) printing technique with a thickness of 2–3 μm. We systematically studied the effect of casting concentration and number of electrospray cycles on membrane thickness and CO2 separation performance. Using a low concentration of polymer of intrinsic microporosity (PIM-1) or PIM-1/HKUST-1 solution (0.1 wt%) leads to TFC membranes with a thickness of less than 500 nm, but the fabricated membranes showed poor CO2 /N2 selectivity, which could be attributed to microscopic defects. To avoid these microscale defects, we increased the concentration of the casting solution to 0.5 wt% resulting in TFC MMMs with a thickness of 2–3 μm which showed three times higher CO2 permeance than the neat PIM-1 membrane. These membranes represent the first examples of 3D printed TFC MMMs using the electrospray printing technique.